A comparative study of kinesthetic intelligence among male and female students in the second intermediate grade in the schools for gifted students in the center of Al-Muthanna Governorate - Nasser, Asst .L. Haider Faleh Hassan; Sadiq, L.Dr. Ahmed Ali (Sulaimani Journal for Humanities, 2025)
The current research aims to identify the level of kinesthetic intelligence among second-year intermediate students in gifted schools in the city center of Al-Muthanna Governorate, and to identify any differences in kinesthetic intelligence between male and female students. To achieve this objective, the researcher employed a descriptive methodology and two survey methods: collecting data on kinesthetic intelligence among male and female students, and a reciprocal method to compare male and female students in kinesthetic intelligence. The research population consisted of second-year intermediate students in gifted schools in the city center of Al-Muthanna Governorate during the 2024-2025 academic year. The population comprised 230 students (male and female) distributed across six schools (three for boys and three for girls). Using a random and equal sampling method, the researcher selected 20 students (male and female), resulting in a sample size of 120 students (male and female). The researcher then identified the kinesthetic intelligence variables as (dropping the ball, walking to the circle). He then conducted a pilot study, and after confirming the validity of the tests based on scientific principles, he proceeded with the main experiment. The researcher concluded that boys outperformed girls in the ball dropping test, while girls outperformed boys in the walking to the circle test. 1. Research Introduction